2014
DOI: 10.7314/apjcp.2014.15.16.6949
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-15a Mediates Cell Cycle Arrest and Potentiates Apoptosis in Breast Cancer Cells by Targeting Synuclein-γ

Abstract: Background: Recent studies have indicated that microRNA-15a (miR-15a) is dysregulated in breast cancer (BC). We aimed to evaluate the expression of miR-15a in BC tissues and corresponding para-carcinoma tissues. We also focused on effects of miR-15a on cellular behavior of MDA-MB-231 and expression of its target gene synuclein-γ (SNCG). Materials and Methods: The expression levels of miR-15a were analysed in BC formalin fixed paraffin embedded (FFPE) tissues by microarray and quantitative real-time PCR. CCK-8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 26 publications
(25 reference statements)
0
20
0
1
Order By: Relevance
“…Increasing evidences indicated that some miRNAs act as either tumor suppressors or promoters in the development of various cancers and play crucial roles in causing messenger RNA (mRNA) degradation or translational inhibition by interacting with the 3′-untranslated region (3′-UTR) of the target mRNA [2][3][4]. Treatment by targeting microRNAs (miRNAs) has attracted extensive research attention in various cancers, including breast cancer [5][6][7][8]. However, the molecular underpinnings of cell proliferation and cell cycle in breast cancer remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidences indicated that some miRNAs act as either tumor suppressors or promoters in the development of various cancers and play crucial roles in causing messenger RNA (mRNA) degradation or translational inhibition by interacting with the 3′-untranslated region (3′-UTR) of the target mRNA [2][3][4]. Treatment by targeting microRNAs (miRNAs) has attracted extensive research attention in various cancers, including breast cancer [5][6][7][8]. However, the molecular underpinnings of cell proliferation and cell cycle in breast cancer remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…The miR-15 superfamily is located in the 13q14 region of human chromosomes, and includes miR-15a, miR-15b, miR-16, miR-195, miR-424 and miR-497. A previous study revealed that miRNA-15a regulates the cell cycle and apoptosis of breast cancer cells through its target gene, SNCG (16). Using bioinformatic tools, the present study revealed that miR-497 is located within close proximity of miR-15a and possibly participates in the regulation of SNCG.…”
Section: Discussionmentioning
confidence: 50%
“…Bioinformatics is the predominant method used for the functional analysis of miRNA. A previous study revealed evidence of the regulation of SNCG by one of its upstream mRNAs, miR-15a (16). Using miRanda (www.microrna.org/microrna/getExprForm.do; version 2010), TargetScan (www.targetscan.org/vert_61; version 6.2), PieTar (www.pictar.mdc-berlin.de; version 2007) and BibiServ (www.bibiserv.techfak.uni-bielefield.be/bibi/ Tools.html; version 2013) databases, the miR-15 family genes were screened (miR-15a, miR-15b, miR-16, miR-195, miR-424 and miR-497), and miR-497 was selected for evaluation in the present study, due to it having similar SNCG-binding sites to miR-15a (Fig.…”
Section: Patientsmentioning
confidence: 99%
“…StarBase2.0 was used to predict and select miRNAs that interacted with the SNCG (Supplementary Table S1). Among these miRNA candidates, we found that miR-15a directly binds to the SNCG [24]. We performed bioinformatics analysis to identify the homologous sequences of lncRNA-AK058003, HuR and miR-15a.…”
Section: Resultsmentioning
confidence: 99%